Prognostic implication of FEV1/FVC ratio for limited-stage small cell lung cancer - Cho, Oyeon (J Thorac Dis, 2018)
BACKGROUND: A proportion of patients with chronic obstructive pulmonary disease (COPD) may progress rapidly to small cell lung cancer (SCLC). As the forced expiratory volume in 1 second (FEV1)/forced volume vital capacity (FVC) ratio is usually impaired in patients with COPD, and given that the FEV1 and FVC are not necessarily related to lung cancer development, we performed this study to test our hypothesis that the FEV1/FVC ratio predicts survival of patients with limited-stage (LS)-SCLC. METHODS: We assessed 74 patients with LS-SCLC treated with chemoradiotherapy. The patients were divided into two FEV1/FVC ratio groups: <0.74 (n=24) and ≥0.74 (n=50). RESULTS: The 3-year overall survival (OS) and 3-year progression-free survival (PFS) rates were significantly lower in patients with FEV1/FVC <0.74 than in those with FEV1/FVC ≥0.74 group (35.4% vs. 61.2%, P=0.0033; and 11.7% vs. 51.8%, P=0.0072, respectively). On multivariate analysis, the low FEV1/FVC group was independently associated with OS and PFS [hazard ratio (HR) (95% confidence interval): 2.15 (0.99–4.63), P=0.052; and 2.13 (1.04–4.39), P=0.039, respectively]. CONCLUSIONS: Pretreatment FEV1/FVC ratio appears to be a potential prognostic factor for patients with LS-SCLC.